DETERMINAN KEPUASAN DAN KINERJA PENGGUNA MODUL GLP SAKTI - Hari Sugiyanto; Miftahul Hadi; Ria Dewi Ambarwati; Anjahul Khuluq (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2022)
This study aims to analyze the factors that influence user satisfaction and net benefit (user performance) of user GLP module of SAKTI which come from system quality, information quality and service quality. Respondents are from 10 ministries/agencies that have used module GLP of SAKTI web version. Sampling is non-probability sampling (voluntary sampling). The data used came from the questionnaires filled by the respondents and obtained 49 samples. Data analysis used SEM-PLS or Structural Equation Model-Partial Least Square using SmartPLS software. The results showed that system quality, service quality have significant and positive effect on user satisfaction, but information quality has no effect on user satisfaction and user satisfaction has significant and positive effect on net benefit. Keywords: AIS, Govermental Accounting, Modul GLP